Chloroplast DNA in Mature and Senescing Leaves: A Reappraisal . Issue 3 (25th March 2014) - Golczyk, Hieronim; Greiner, Stephan; Wanner, Gerhard; Weihe, Andreas; Bock, Ralph; Börner, Thomas; Herrmann, Reinhold G.
Abstract: The fate of plastid DNA (ptDNA) during leaf development has become a matter of contention. Reports on little change in ptDNA copy number per cell contrast with claims of complete or nearly complete DNA loss already in mature leaves. We employed high-resolution fluorescence microscopy, transmission electron microscopy, semithin sectioning of leaf tissue, and real-time quantitative PCR to study structural and quantitative aspects of ptDNA during leaf development in four higher plant species ( Arabidopsis thaliana, sugar beet [ Beta vulgaris ], tobacco [ Nicotiana tabacum ], and maize [ Zea mays ]) for which controversial findings have been reported. Our data demonstrate the retention of substantial amounts of ptDNA in mesophyll cells until leaf necrosis. In ageing and senescent leaves of Arabidopsis, tobacco, and maize, ptDNA amounts remain largely unchanged and nucleoids visible, in spite of marked structural changes during chloroplast-to-gerontoplast transition. This excludes the possibility that ptDNA degradation triggers senescence. In senescent sugar beet leaves, reduction of ptDNA per cell to ∼30% was observed reflecting primarily a decrease in plastid number per cell rather than a decline in DNA per organelle, as reported previously. Our findings are at variance with reports claiming loss of ptDNA at or after leaf maturation.